Psycholinguistic Characteristics of the Discourse with a «Colour Black» Component (based on E.M. Remarque’s works) - Halyna I. Kapnina (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
In recent decades, colour vocabulary has been actively studied by the Ukrainian and foreign scientists. Modern Linguistics has significant achievements in research of this issue, however, some of its aspects, in particular, psycholinguistic characteristics of the discourse with a colour element, still remain relevant and poorly researched. Colour has always played an important role in artistic discourse. The names of individual writers are inextricably associated with certain coloronyms, which is a so-called marker in their work. One example of this phenomenon is the colour black, that is dominant in the discourse of E.M. Remarque, which, given the mostly dramatic themes of the author’s novels, is quite expected, especially if the fact is considered through the prism of Psycholinguistics. The purpose of the given scientific investigation is to provide psycholinguistic characteristics of the discourse with the «black colour» component in E.M. Remarque’s works and to identify the impact it has on the reader in the process of perceiving the outstanding author’s texts. Implementation of the stated tasks of research involved the integrational usage of general scientific methods (such as description, induction, deduction), as well as the analysіs of dictionary definitions, current native and foreign psycholinguistic sources; contextual and structural-thematic analysis; modelling and classification of actual material. The results of the analysis of the Remarque’s discourse with the «black colour» component allow us drawing the following conclusion: the coloronym «schwarz» in E.M. Remarque’s is characterised by a wide semantic content, wherein the black colour is used by the writer both to determine the colour of the described object neutrally and to convey figurative negative semantics. Lexemes denoting black, in their direct meaning, indicate the colour of the depicted object directly. Using the colour nomination «schwarz» in symbolic meaning, the author resorts to «painting» in dark natural phenomena, which are not characterised by black; depicts dishonest and illegal actions; demonstrates negative attitude towards people. Using the specified colour nomination as the colour of clothing, objects, buildings, as well as emotions, experiences and feelings, non-verbal means of intensification the semantics of “black” – the designation of poses, gestures, facial expressions, body movements the author demonstrates not only his personal attitude towards the characters of his novels, but by focusing the consciousness of the reader on their difficult psychological and physical state, he encourages to rethink the causes and consequences of their actions. Stable association with the black colour, peculiar for a long historical and cultural development of mankind, and therefore with sad events in human life, losses, failures, loneliness, is verbalized in all analysed Remarque’s works. Thus, the black colour is the necessary element of the psycholinguistic portrait of Remarque’s character.